Comparison of intracranial aneurysm flow quantification techniques: standard PIV vs stereoscopic PIV vs tomographic PIV vs phase-contrast MRI vs CFD. (30th July 2018) - Roloff, Christoph; Stucht, Daniel; Beuing, Oliver; Berg, Philipp
Abstract : Image-based hemodynamic simulations to assess the rupture risk or improve the treatment planning of intracranial aneurysms have become popular recently. However, due to strong modeling assumptions and limitations, the acceptance of numerical approaches remains limited. Therefore, validation using experimental methods is mandatory. In this study, a unique compilation of four in-vitro flow measurements (three particle image velocimetry approaches using a standard (PIV), stereoscopic (sPIV), and tomographic (tPIV) setup, as well as a phase-contrast magnetic resonance imaging (PC-MRI) measurement) were compared with a computational fluid dynamics (CFD) simulation. This was carried out in a patient-specific silicone phantom model of an internal carotid artery aneurysm under steady flow conditions. To evaluate differences between each technique, a similarity index (SI) with respect to the velocity vectors and the average velocity magnitude differences among all involved modalities were computed. The qualitative comparison reveals that all techniques are able to provide a reasonable description of the global flow structures. High quantitative agreement in terms of SI and velocity magnitude differences was found between all PIV methods and CFD. However, quantitative differences were observed between PC-MRI and the other techniques. Deeper analysis revealed that the limited resolution of the PC-MRI technique is a major contributor to the experienced differences and leads to a systematic underestimation of overall velocity magnitude levels inside the vessel. This confirms the necessity of using highly resolving flow measurement techniques, such as PIV, in an in-vitro environment to individually verify the validity of the numerically obtained hemodynamic results.